ACTIVELY CONTROL HYPERTENSION TO LIVE LONGER IN THE COMMUNITY OF KAPASA RAYA VILLAGE - Sari Wijayaningsih, Kartika; Mutmainna, Amriati; Mina La Isa, Wa; Ernawati, Ernawati; Mato, Rusni; Darwis, Darwis; Muzakkir, Muzakkir; Indrayani, Ferna (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
Hypertension has become one of the causes of high mortality and illness and can cause complications such as heart disease, stroke, and kidney failure. The increase in hypertension in Indonesia, including Kapasa Village, is very worrying. Referring to the Government program, this CERDIK activity is considered necessary in order to prevent hypertension complications. The purpose of this research is to implement a community-based government program as an effort to detect and prevent hypertension disease. The method used, the implementation is divided into three stages, namely preparation, implementation, and evaluation. The results of the study showed that the respondents suffered from hypertension with a fairly high range and some respondents had experienced increased cholesterol and a lack of knowledge. This discussion suggests that hypertension is caused by negative behavioral triggers, such as the consumption of unhealthy foods and smoking and alcohol behaviors. The recommendations in this activity are to emphasize the community's compliance to carry out routine blood tests, light exercise in the morning, and the need to increase knowledge as a counter measuring tool for CERDIK to reduce the growth rate of hypertension cases in the community